Isoproterenol Induced Insulin Resistance Leading to Diabetic Ketoacidosis in Type 1 Diabetes Mellitus. (17th December 2018) - Hoff, Ryan; Koh, Chung-Kay
Abstract : Isoproterenol is known to cause insulin resistance and is often used to treat bradyarrhythmias from atrioventricular block. We report a case of isoproterenol induced diabetic ketoacidosis in a 77-year-old female patient treated with isoproterenol for atrioventricular block prior to insertion of permanent pacemaker. Diabetic ketoacidosis (DKA) developed within hours of starting an isoproterenol drip, and there were no other precipitating factors at that time. DKA resolved quickly after discontinuing isoproterenol and starting insulin drip. DKA is a common complication of diabetes mellitus, with about 140, 000 hospital admissions for DKA in 2009. While the rate of DKA has increased by nearly 50% between 1988 and 2009, the rate of mortality has decreased. There are many causes of diabetic ketoacidosis, such as medication noncompliance, infection, pancreatitis, stroke, myocardial infarction, and many others. Isoproterenol may lead to diabetic ketoacidosis by increasing insulin resistance.